COMMUNICATION PATTERNS OF SOCIAL ASSISTANT PROGRAM FOR THE HARAPAN FAMILY IN THE ACTIVITIES OF FAMILY CAPABILITY IMPROVEMENT MEETINGS (P2K2) BENEFICIARY FAMILY (KPM) BALIGE DISTRICT - Andino Sinaga, Rammen (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
This study aims to look at the communication patterns of the social companions of the Family Hope Program in the Family Capacity Building Meeting (P2K2) in Balige District. Family Capacity Building (P2K2) carried out by Social Assistance to beneficiary families (KPM) basically has the same goal as the Sustainable Development Goals (SDGs) which is to improve the welfare and safety of the community in order to improve the ability of the underprivileged to manage their daily lives. . With the following conclusions: (1) Family Capacity Building Activities have interaction between social assistants and families who are beneficiaries of the social assistance. This interaction creates an emotional closeness between the parties involved. In this activity, communication between the parties involved. The effective communication starts from the closeness and shared experience between the Social Facilitator and the beneficiary. With the results of the study as follows, the communication used in Family Capacity Building activities is a type of interpersonal communication and group communication. (2) In P2K2 activities, social assistants must take an emotional approach to KPM PKH because emotional closeness will increase the extrinsic motivation of KPM PKH. (3) Communication barriers in P2K2 activities, social assistants must take more persuasive and humane actions, so that the message conveyed can be well received. (4) P2K2 Balige District can be said to be effective communication, because the purpose.